Knowledge of preconception care among eligible women - Kayarupi, K.; Thilini, C.; Kamalarupan, L.; Nivetha, K. (University of Jaffna, 2024)
Introduction: Preconception care (PCC) is the provision of biomedical, behavioral, and social health interventions to women and couples before conception occurs. It prevents maternal and perinatal complications and increases the possibility of healthy couples and healthy offspring. Objective: To assess the knowledge of preconception care among eligible women in the Nallur MOH area, Sri Lanka. Methodology: This was a community-based descriptive cross-sectional study among 422 eligible women. An interviewer-administered questionnaire was used for data collection. The data were analyzed using SPSS 20. Results: The response rate was 100%. The mean age was 25.5 (SD=±2.259) years. The majority (96.2%) of them were Tamils and Hindus (86.7%). All participants were married, and the mean age of marriage was 20.4 years. 53.6% of them were from the nuclear family. 55.9% of them were aware of preconception care. Nearly 60% of the participants were aware of the targeted group of PCC. Most of them thought providing folic acid supplementation was the only objective of PCC, and the majority (60.4%) were aware of when to start it and the importance of it (76.3%). 38.9% of them knew the recommended age range for women for childbearing. Only 20.6% of participants were aware of the recommended BMI range for women for childbearing. 54.5% of them believed that personal hygiene could prevent sexually transmitted infections. Only 20.1% of participants knew their blood group was screened during PCC. The majority of them were aware that smoking (67.1%) or passive smoking (45.0%) is harmful during PCC. Only one-third of them had overall good knowledge, and the rest had poor knowledge of PCC. Conclusion: Knowledge of preconception care is inadequate for the participants in the Nallur MOH area. It is important to conduct health education programs on preconception care in order to increase the awareness of eligible women.
Keywords: Knowledge; Preconception care; Eligible women